2021
DOI: 10.37970/aps.v5i1.79
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a short form self-reported financial wellbeing scale for inclusion in the 2026 Census

Abstract: No abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Based on previous studies (Botha & New, 2021), (OECD, 2020), (Mahdzan et al, 2020), (Heath et al, 2018), (Predergast et al, 2018), (CFPB, 2017), (CFPB, 2015) financial wellness refers to household's (i) financial health (like income, savings) to fulfill daily and emergency requirements in current as well as future, (ii) financial security and financial freedom in the life course, and (iii) ability of effective financial management. (Masenya & Dickason-Koekemoer, 2020), (Heo et al, 2020) study revealed that financial wellness positively correlates with satisfaction with life, whereas life satisfaction refers to an individual's satisfaction towards happiness and subjective well-being.…”
Section: Literature Review Financial Wellnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies (Botha & New, 2021), (OECD, 2020), (Mahdzan et al, 2020), (Heath et al, 2018), (Predergast et al, 2018), (CFPB, 2017), (CFPB, 2015) financial wellness refers to household's (i) financial health (like income, savings) to fulfill daily and emergency requirements in current as well as future, (ii) financial security and financial freedom in the life course, and (iii) ability of effective financial management. (Masenya & Dickason-Koekemoer, 2020), (Heo et al, 2020) study revealed that financial wellness positively correlates with satisfaction with life, whereas life satisfaction refers to an individual's satisfaction towards happiness and subjective well-being.…”
Section: Literature Review Financial Wellnessmentioning
confidence: 99%
“…According to (PwC, 2020), (PwC, 2014) employee financial wellness survey, financial wellness is significantly correlated with financial literacy for decision-making and financial behavior towards savings, investments, credit, and others. Multiple reports and research (Botha & New, 2021), (OECD, 2020), (Heath et al, 2018), (Gautam & Andersen, 2016) (Brüggen et al, 2017), (CFPB, 2017), (Coşkuner, 2016), (CFPB, 2015) examined financial wellness with multiple corresponding constructsfinancial behavior, financial attitude, financial knowledge, financial solvency, income, education, and individual characteristics.…”
Section: Literature Review Financial Wellnessmentioning
confidence: 99%